Advances in immunotherapy for melanoma. Issue 1 (December 2016) - Redman, Jason; Gibney, Geoffrey; Atkins, Michael
Abstract In recent years, the introduction and Federal Drug Administration approval of immune checkpoint inhibitor antibodies has dramatically improved the clinical outcomes for patients with advanced melanoma. These antagonist monoclonal antibodies are capable of unleashing dormant or exhausted antitumor immunity, which has led to durable complete and partial responses in a large number of patients. Ipilimumab targets the cytotoxic T lymphocyte-associated protein 4 (CTLA-4) receptor. Nivolumab and pembrolizumab target programmed cell death protein 1 (PD-1) receptors and have proven to be superior to ipilimumab alone. The combination of ipilimumab and nivolumab has yielded higher response rates, greater tumor shrinkage, and longer progression-free survival than either monotherapy alone. As other promising immunotherapies for melanoma proceed through clinical trials, future goals include defining the role of immune checkpoint inhibitors as adjuvant therapy, identifying optimal combination strategies, and developing reliable predictive biomarkers to guide treatment selection for individual patients.